Women’s Political Empowerment in Balochistan: A Focus on Political Literacy Among Policymakers - Batool, Dr. Rubeena; Baloch, Mr. Shah Khalid; Samar, Ms. Nasreen (Journal of Quranic and Social Studies, 2023)
Political Empowerment of women in Balochistan is debatable in sense of how policy and the process of policymaking defined with reference to the knowledge, attitude and practices of policymakers. In 2001 the Devolution plan in Pakistan gave 33% representation for women in the local government system nationwide. The women political empowerment (WPE) is mostly taken in institutional context in the available literature; the significance of this research is to highlight the prevalence level of political literacy as a source to assess the policy makers to see the actual progress of the women political empowerment. In Balochistan the legislated empowerment is not succeeded because the policy makers are known about the institutional context and not known about the societal context of WPE. KAP (Knowledge, Attitude, and Practice) framework is used to examine the political literacy of policy makers in context to WPE. Purposive sampling is being used in this respect. The study would be useful to enable government to make effective policymaking to meet the contemporary challenges of women political empowerment in and around Balochistan.